2016
DOI: 10.4238/gmr.15038540
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of the dehydration-responsive element-binding protein 2A gene in Eruca vesicaria subsp sativa

Abstract: ABSTRACT. Eruca vesicaria subsp sativa is one of the most tolerant Cruciferae species to drought, and dehydration-responsive elementbinding protein 2A (DREB2A) is involved in responses to salinity, heat, and particularly drought. In this study, a gene encoding EvDREB2A was cloned and characterized in E. vesicaria subsp sativa. The fulllength EvDREB2A cDNA sequence contained a 388-bp 5'-untranslated region (UTR), a 348-bp 3'-UTR, and a 1002-bp open reading frame that encoded 334 amino acid residues. The theoret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…6). Upregulation of the Dehydration-Responsive Element -Binding protein 2A (DREB2A) can activate the various genes related to stress tolerance in different plant species [45]. It has also been reported that over-expression of OsTIFY11 (located in Chr3:M-QTL1, up-regulated in the shoot and root) increased the tolerance to salinity stress through the Jasmonic Acid (JA) signaling and through modulating the potassium homeostasis (Table S6, Fig.…”
Section: Transcription Regulationmentioning
confidence: 99%
“…6). Upregulation of the Dehydration-Responsive Element -Binding protein 2A (DREB2A) can activate the various genes related to stress tolerance in different plant species [45]. It has also been reported that over-expression of OsTIFY11 (located in Chr3:M-QTL1, up-regulated in the shoot and root) increased the tolerance to salinity stress through the Jasmonic Acid (JA) signaling and through modulating the potassium homeostasis (Table S6, Fig.…”
Section: Transcription Regulationmentioning
confidence: 99%
“…HSFA6B (located in Chr1:M-QTL3, up-regulated in the seedlings) acts as a positive regulator downstream of Abscisic Acid (ABA) signaling directly bound to the promoter of Dehydration-Responsive Element-Binding (DREB) and increasing its expression (Table S6, Fig.6). Upregulation of the Dehydration-Responsive Element -Binding protein 2A (DREB2A) can activate the various genes related to stress tolerance in different plant species [45]. It has also been reported that overexpression of OsTIFY11 (located in Chr3:M-QTL1, up-regulated in the shoot and root) increased the tolerance to salinity stress through the Jasmonic Acid (JA) signaling and through modulating the potassium homeostasis (Table S6, Fig.6) [46].…”
Section: Transcription Regulationmentioning
confidence: 98%
“…saatlere göre önemli bir farkın oluşmadığı bildirilmiştir (Liu et al 2008). Eruca vesicaria subsp sativa'da ise, EvDREB2A geninin en yüksek ifade seviyesinin yapraklarda, en düşük ise çiçek tomurcuklarında olduğunu bildirmişlerdir (Huang et al 2016). DREB2A transkripsiyon faktörünün aşırı ifade edilmesi ile, bitkilerde kuraklık stresine karşı önemli dayanıklılıkların sağlandığını bildiren çalışmalar da bulunmaktadır (Sakuma, 2006a(Sakuma, , 2006bQin et al 2007;Agarwal et al 2010;Chen et al 2016).…”
Section: Tartişma Ve Sonuçunclassified